An integrated low-energy ventilation system to improve indoor air quality and thermal comfort of primary school buildings in the cold climate zone of China - Peng, Zhen (2019)
Indoor air quality (IAQ) and thermal comfort in schools are serious concerns in China because they have significant effects on student health, academic performance and learning productivity. Due to the financial limitations and the requirements of building design regulations, primary school buildings in China are commonly naturally ventilated. However, the applicability of natural ventilation dramatically depends on the suitability of the local climate. On ambient air pollution days and in the cold winter or hot summer seasons, natural ventilation cannot deliver clean air and provide a thermally comfortable environment. Air purifiers have become popular for mitigating indoor air pollution. However, air purifiers are not always efficient and cannot dilute CO2 concentrations in closed spaces. Additionally, some purifiers may generate ozone gases as they remove other air pollutants. Furthermore, many governments have rejected the installation of air purifiers in classrooms because of the power shortages, financial limitations and inadequate space. To solve these issues, an integrated low-energy ventilation (ILEV) system was invented. The system includes four main parts: a solar chimney, natural ventilation, earth-to-air heat exchangers (EAHEs), and a sunspace with plants. These four parts form the ILEV system, which can be employed by primary school buildings in the cold climate zone of China. In the system, fresh air is preheated or precooled to the temperature of the undisturbed soil by EAHEs and is then supplied to the sunspace. The air is cleaned in the sunspace by the plants and is further supplied to the classrooms. Finally, the waste air inside classrooms is released through the solar chimney by stack effects. To explore the performance of the ILEV system, a typical school building located in the cold climate zone of China was selected. The case study building was redesigned to install the ILEV system based on the School Building Design Regulation-2011 (SBDR-2011) and the Public Building Energy Saving Standard-2015 (PBESS-2015). The research methods in this work involve the dynamic thermal modelling (DTM), computer fluid dynamics (CFD) simulations and experimental measurements. The experimental methods were used to explore the abilities of plants to remove air pollutants (PM2.5 and PM10). The DTM provided hourly classroom data regarding the average indoor air temperature, relative humidity, airflow rates, CO2 levels and heat gains throughout the calendar year. The CFD simulations verified the fluidity of the ILEV system and provided a steady state analysis of the internal air flow distribution in classrooms. An energy simulation model created in GBSWARE was used to quantify the energy consumption of the case study building. Revit models of the case study building were used to generate material take-off sheets. These sheets indicate the additional incremental material costs and estimate the payback period of the ILEV system. The simulation results and experimental data indicate that the air temperatures inside the classrooms were maintained in the range of 15°C to 27°C throughout the year. The internal CO2 concentrations averaged approximately 900 ppm in all classrooms. In addition, the indoor PM2.5 and PM10 concentrations were only 48% and 64% of the current PM concentrations in primary school classrooms, respectively. The ILEV system consumed approximately 2% of the energy currently consumed by the cast study primary school buildings. Consequently, over 90% of the CO2 emission was reduced. The payback period of the ILEV system was 9.7 years. Compared to other renewable technologies, the ILEV system only requires 19% of its lifespan to recoup the initial costs and provides economic benefits over 40 years. In summary, a low-energy system was designed to provide clean air and a thermally comfortable indoor environment in the primary school buildings located in the cold climate zone of China. This system can save energy, reduce CO2 emissions and provide significant economic benefits.